2009
DOI: 10.1080/16506070802694776
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Aided Psychotherapy for Anxiety Disorders: A Meta‐Analytic Review

Abstract: Abstract. Computer-aided psychotherapy (CP) is said to (1) be as effective as face-to-face psychotherapy, while requiring less therapist time, for anxiety disorder sufferers, (2) speed access to care, and (3) save traveling time. CP may be delivered on stand-alone or Internet-linked computers, palmtop computers, phone-interactive voice response, DVDs, and cell phones. The authors performed a meta-analysis of 23 randomised controlled studies (RCTs) that compared CP with non-CP in anxiety disorders: phobias, n51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
263
1
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(304 citation statements)
references
References 65 publications
18
263
1
19
Order By: Relevance
“…However, these low recruitment rates may not be unusual for a fully online intervention and may be consistent with the finding that only 10 to 20 percent of adults are interested in an Internet-based lifestyle change at any given time [45][46]. Furthermore, the moderate depression pre/post ESs were less than those seen in treatment interventions involving therapist and discussion group contact (VETS PRE-VAIL ES = 0.45 vs Internet plus therapist contact ES = 0.93) [21,[47][48] but comparable with preventive interventions using an Internet-only approach (male adolescents ES = 0.29) [47,49]. Similarly, this intervention demonstrated pre/post ESs comparable to an Internet-only PTSD intervention but lower than those reported in one with therapist contact (VETS PREVAIL ES = 0.30 vs ES = 0.45 for Internet-only or ES = 0.76 for Internet plus therapist) [50][51].…”
Section: Discussionsupporting
confidence: 61%
“…However, these low recruitment rates may not be unusual for a fully online intervention and may be consistent with the finding that only 10 to 20 percent of adults are interested in an Internet-based lifestyle change at any given time [45][46]. Furthermore, the moderate depression pre/post ESs were less than those seen in treatment interventions involving therapist and discussion group contact (VETS PRE-VAIL ES = 0.45 vs Internet plus therapist contact ES = 0.93) [21,[47][48] but comparable with preventive interventions using an Internet-only approach (male adolescents ES = 0.29) [47,49]. Similarly, this intervention demonstrated pre/post ESs comparable to an Internet-only PTSD intervention but lower than those reported in one with therapist contact (VETS PREVAIL ES = 0.30 vs ES = 0.45 for Internet-only or ES = 0.76 for Internet plus therapist) [50][51].…”
Section: Discussionsupporting
confidence: 61%
“…Internet-based interventions are also effective in changing negative health behaviors (eg, reducing alcohol consumption) (20), although mixed results were obtained for smoking cessation (21). Internet-based psychotherapy has been investigated in a large number of randomized controlled trials (RCT) (16)(17)(18). However, only a few interventions have been developed and evaluated to address the specific needs of working populations.…”
mentioning
confidence: 99%
“…Internet-based interventions have been shown to be effective in clinical applications, including the treatment of depression (15)(16)(17), anxiety (18), and sleep disorders (19). In particular, internet-based interventions for depression that include support from a healthcare professional (guided self-help) lead to greater effects and stronger adherence than self-help treatments on their own (15,17).…”
mentioning
confidence: 99%
“…While this finding is in keeping with Cuijpers et al's (2009) metaanalysis, which found that iCBT for anxiety disorders is effective, the effect size compared to control for our study was moderate while that found in the meta-analysis was large. Cuijpers et al (2009) found that the reduction in time spent with therapist in computer-aided therapies as compared to face-to-face therapies was negatively associated with effect size. Our smaller effect size might therefore reflect the 'light touch' nature of the support we provided to participants, which came in the form of texted reminders to persevere with the program, rather than any direct contact or therapeutic content.…”
Section: Discussionmentioning
confidence: 92%